Unusual Type of Hand Preaxial Polydactyly - Sirasanagandla, Srinivasa Rao; Nayak, Satheesha B.; Al Mushaiqri, Mohamed (Journal of Morphological Sciences, 2018)
Preaxial polydactyly is a common congenital anomaly of the hand. In this anomaly, an additional digit is seen along the preaxial border of the thumb. Several possible types of preaxial polydactyly have been observed and categorized into several types based on the level of duplications. In the present case, we report an unusual type of polydactyly in an approximately 55year-old male cadaver of South Indian origin. An additional non-functional digit was noted along the preaxial border of the thumb, at the level of the base of the distal phalanx. Upon careful dissection of the anomalous digit, a thick cord of connective tissue formed by the fibrous flexor sheath around the flexor pollicis longus tendon was noted in its central core. This cord was surrounded by a mass of fatty tissue. The skeletal, muscle and tendon components were found to be absent in the additional digit.
Keywords: radial polydactyly; congenital anomalies; cadaver; hand